2022
DOI: 10.3390/cancers14030490
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Immunoactive and Immunotolerant CD4+ T Cells in Breast Cancer by Measuring Activity of Signaling Pathways That Determine Immune Cell Function

Abstract: Cancer immunotolerance may be reversed by checkpoint inhibitor immunotherapy; however, only a subset of patients responds to immunotherapy. The prediction of clinical response in the individual patient remains a challenge. CD4+ T cells play a role in activating adaptive immune responses against cancer, while the conversion to immunosuppression is mainly caused by CD4+ regulatory T cell (Treg) cells. Signal transduction pathways (STPs) control the main functions of immune cells. A novel previously described ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…We previously reported a completely new method to quantitatively measure activity of clinically relevant signal transduction pathways (STP) on transcriptome data of individual cell-containing samples ( Bouwman et al, 2020 ), ( Verhaegh et al, 2014 ), ( Stolpe et al, 2019 ), ( Canté-Barrett et al, 2020 ), ( Wesseling-Rozendaal et al, 2021 ), ( Van Ooijen et al, 2018 ), ( Bouwman et al, 2020 ), ( Wesseling-Rozendaal et al, 2022 ), ( Bouwman et al, 2021 ). Using this technology to analyze RNA expression data of colon mucosa biopsy samples, signaling pathway activity was investigated in CD and UC, and related to pathophysiology of IBD and the clinical response to anti-TNFα treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported a completely new method to quantitatively measure activity of clinically relevant signal transduction pathways (STP) on transcriptome data of individual cell-containing samples ( Bouwman et al, 2020 ), ( Verhaegh et al, 2014 ), ( Stolpe et al, 2019 ), ( Canté-Barrett et al, 2020 ), ( Wesseling-Rozendaal et al, 2021 ), ( Van Ooijen et al, 2018 ), ( Bouwman et al, 2020 ), ( Wesseling-Rozendaal et al, 2022 ), ( Bouwman et al, 2021 ). Using this technology to analyze RNA expression data of colon mucosa biopsy samples, signaling pathway activity was investigated in CD and UC, and related to pathophysiology of IBD and the clinical response to anti-TNFα treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Development and validation of computational models to quantitatively measure activity of the androgen receptor (AR), MAPK, NFκB, WNT, TGFβ, JAK-STAT1/2, and JAK-STAT3 pathways have been described before and is simplified shown in Supplementary Figure S1 . The models can in principle be used to analyze pathway activity on any cell type, based on analysis of transcriptome data ( Bouwman et al, 2020 ), ( Verhaegh et al, 2014 ), ( Stolpe et al, 2019 ), ( Canté-Barrett et al, 2020 ), ( Wesseling-Rozendaal et al, 2021 ), ( Van Ooijen et al, 2018 ), ( Bouwman et al, 2020 ), ( Wesseling-Rozendaal et al, 2022 ), ( Bouwman et al, 2021 ). For the current study, pathway activity scores (PAS) were measured on publicly available Affymetrix expression microarray data from preclinical and clinical IBD studies.…”
Section: Methodsmentioning
confidence: 99%
“…Some metabolic proteins have been found to be overexpressed on intratumoral Tregs of patients with BC ( Malla et al, 2022 ) . In primary BC, the adaptive immune response of CD4 + T cells may often be replaced by immunosuppressive Treg cells, which may induce resistance to checkpoint inhibition ( Wesseling-Rozendaal et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…146 TNBC is sensitive to PF-03084014, and the Notch inhibitor PF-03084014 combined with the AKT 149 Nevertheless, GISs cannot target specific receptors; thus, they also bring about adverse effects such as nausea and vomiting, which appear to be very limiting as monotherapy drugs. 140 The development of antibodies that specifically inhibit members of the Notch family indicates a step toward a solution to this problem. There are currently two main classes of such antibodies.…”
Section: Notch Signaling Pathway Inhibitorsmentioning
confidence: 99%
“… 107 Recently, analytical methods capable of quantitatively measuring the activity of signal transduction pathways in tissue and blood samples have been developed, and the pathway analysis revealed that Treg cells in breast cancer have high Notch pathway activity scores, and Notch is expected to be a new target for the characterization of immune activity and immunosuppressive therapy in BC. 107 , 140 In summary, Notch signaling has important implications for Th17/Treg in BC.…”
Section: Notch Regulates Slec Differentiation Of Cd8+ T Cellsmentioning
confidence: 99%